The Heterogeneity of Socially Responsible Investment - Sandberg, Joakim (Journal of business ethics, 2008)
Many writers have commented on the heterogeneity of the socially responsible investment (SRI) movement. However, few have actually tried to understand and explain it, and even fewer have discussed whether the opposite – standardisation – is possible and desirable. In this article, we take a broader perspective on the issue of the heterogeneity of SRI. We distinguish between four levels on which heterogeneity can be found: the terminological, definitional, strategic and practical. Whilst there is much talk about the definitional ambiguities of SRI, we suggest that there is actually some agreement on the definitional level. There are at least three explanations which we suggest can account for the heterogeneity on the other levels: cultural and ideological differences between different regions, differences in values, norms and ideology between various SRI stakeholders, and the market setting of SRI. Discussing the implications of the three explanations for the SRI market, we suggest that there is reason to be sceptical about the possibilities of standardisation if not standardisation is imposed top-down. Whether this kind of standardisation is desirable or not, we argue, depends on what the motives for it would be. To the extent that standardisation may facilitate the mainstreaming of SRI, it could be a good thing – but we entertain doubts about whether mainstreaming really requires standardisation.